Comparative analysis of load capacity of precast piles obtained through theoretical methods in GEO5 software (Research, Society and Development, 2022)
The prediction of load capacity is of great value for the development of a foundation project. Due to the existence of difficulty in determining it accurately several methods developed by different authors have emerged over time. This research aims to compare the accuracy of the analytical   methods of "NAVFAC DM 7.2", "Effective Stresses" and "CSN  73 1002" for the results of load capacity of precast concrete piles. For the performance analysis, the values of geotechnical load capacity adopted as reference were those mobilized in load tests performed in forty-nine (49) piles. These values were compared with those obtained by the mentioned methods, measuring their correlation, mean percentage errors and mean quadratic errors. It has also been proposed adjustments to improve the predictions of each method, providing more accurate results. In first predictions the percentage errors ranged from 40.8% up to 96%. After excluding outliers and proposing adjustment coefficients to be applied to each value, all the methods presented better performances, with percentage error lowering to 30.8% in best result. It was concluded that, in general, the NAVFAC DM 7.2 method presented the best results.